Electrical conductivity and modulus study of 0.76Na0.5Bi0.5TiO3-0.2SrTiO3-0.04BaTiO3 ceramic: A near morphotropic phase boundary composition. (April 2019) - Praharaj, S.; Rout, D.
Abstract: The electrical transport properties of a lead-free ceramic system near its morphotropic phase boundary composition (i.e., 0.76Na0.5 Bi0.5 TiO3 -0.2SrTiO3 -0.04BaTiO3 ) have been investigated by impedance spectroscopy in the temperature range from 50 to 650 °C. The temperature- and frequency-dependent dc and ac conductivity analysis was accomplished with reference to some empirical models. The notable features observed from dc conductivity analysis unveil the dominance of small polaron adiabatic and nonadiabatic models at higher and lower temperatures, respectively. Frequency dispersion of ac conductivity is viewed in the framework of the universal Jonscher law. The temperature-sensitive frequency exponent S indicates that correlated barrier hopping is probably responsible for ac conduction in the high-temperature range, while large polaron overlapping tunneling dominates below 275 °C. The non-Debye type of relaxation as perceived from complex modulus plots can be better explained by a modified Kohlrausch-Williams-Watts function rather than a Gaussian function. The thermally activated relaxation mechanism is further supported by the scaling behavior of both the conductivity and the modulus. The substantial decrease in conductivity by more than 2 orders of magnitude as compared with the 0.8Na0.5 Bi0.5 TiO3 -0.2SrTiO3 binary system is expected to make the poling process easier. Highlights: A detailed conductivity study of a Pb-free 0.76Na0.5 Bi0.5 TiO3 -0.2SrTiO3 -0.04BaTiO3 composition was attempted. Reduction of conductivity by more than 2 orders of magnitude was found as compared with 0.8Na0.5 Bi0.5 TiO3 -0.2SrTiO3 . Empirical models were used to understand the underlying conductivity mechanism. The modulus and its scaling were used to provide useful insight into the relaxation process.